Efficacy of Bath PUVA Treatment in Palmoplantar Psoriasis - (:unkn) unknown (DERI ZUHREVI HASTALIKLAR DERNEGI, 2009)
Background and Design: Although PUVA is widely used in the treatment of psoriasis, data on the efficacy of local PUVA in palmoplantar psoriasis is limited. The aim of current study is to evaluate the efficacy of local bath PUVA alone or in combination with systemic retinoid for treatment of palmoplantar psoriasis. Material and Method: The efficacy of bath PUVA was evaluated retrospectively in 18 patients with palmoplantar psoriasis. Treatment was performed 3 times weekly. Hands and feet were exposed to UVA immediately after a 15-minutes bath in 2 litres of tap water containing 10 mg/litre 8-methoxypsoralen. PUVA was used alone or in combination with acitretin in severe and resistant patients. Acitretin was either given from the beginning or was added to ongoing phototherapy. Bath PUVA was continued till complete or maximum improvement was achieved. Results: Of 18 patients, 7 received bath PUVA treatment alone whereas 11 used acitretin additionally. Six patients used acitretin and bath PUVA together from the beginning whereas in 5 patients who responded insufficiently to PUVA alone, acitretin was added to treatment later. Mean acitretin dose was 25 mg/day. Acitretin was added to ongoing phototherapy after a mean of 20 treatment sessions. Sixteen patients completed the treatment and 12 of them (75%) showed moderate to significant improvement. Mean number of treatments was 32 (8-69), mean cumulative UVA dose was 155.4 J/cm(2) (22-373.5), maximum UVA dose per session was 6.6 J/cm(2) (3-8). Mild to moderate erythema was observed in 2 patients (13%). No patient discontinued treatment due to side effects. Conclusion: Bath PUVA is an effective and safe treatment modality in palmoplantar psoriasis. (Turkderm 2009, 43: 25-8)
Keywords: Palmoplantar psoriasis; bath PUVA; A THERAPY; DERMATOSES; 8-METHOXYPSORALEN; ULTRAVIOLET; GEL